2009
DOI: 10.1515/znb-2009-0901
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Crystal Structure of 2,3,5-Triphenyltetrazolium Hexachlorophosphate and Dichlorophosphate(V), [TPT]+[PCl6] and [TPT]+[PO2Cl2]

Abstract: 2,3,5-Triphenyltetrazolium hexachlorophosphate, [C 19 in dry acetonitrile, and their crystal structures were determined by single-crystal X-ray diffraction analysis. In the title compounds, the [TPT] + cations show a face-to-face stacked orientation between the phenyl rings of neighboring molecules, which is caused by intermolecular π ···π interactions. The crystal structure of compound 1 consists of layers of 2,3,5-triphenyltetrazolium cations and hexachlorophosphate anions. In compound 2 the tetrahedral [P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results obtained by DFT are considered to be more reliable and are consistent with the expected length of the V=O bond (1.6 Å) [30]. [54][55][56][57]. Table 1: Extraction-spectrophotometric optimization of the V IV -TAO -TTC -water -chloroform system.…”
Section: Ground State Equilibrium Geometry Of the Ternary Complexmentioning
confidence: 58%
“…The results obtained by DFT are considered to be more reliable and are consistent with the expected length of the V=O bond (1.6 Å) [30]. [54][55][56][57]. Table 1: Extraction-spectrophotometric optimization of the V IV -TAO -TTC -water -chloroform system.…”
Section: Ground State Equilibrium Geometry Of the Ternary Complexmentioning
confidence: 58%
“…The results showed that the extracted ternary complex has a composition of 1 : 1 : 2 (Fe-4NC-TTC). One can conclude that the Fe(II)-4NC anionic chelate has a double negative charge, since TTC forms monovalent cation (TT + ) [13,[15][16][17][18][19][20][21][22][23][24][25][26] and the Fe(II)-to-TTC molar ratio is 1 : 2 ( Fig. 5, 2).…”
Section: Doi: 101134/s1070363215080241mentioning
confidence: 99%
“…We previously reported [13] a liquid-liquid extraction-chromogenic system containing Fe(III), 4NC, and a widely used [15][16][17][18][19][20][21][22][23][24][25][26] cationic ion-association reagent, 2,3,5-triphenyl-2H-tetrazolium chloride (TTC). The next step, study of a similar system containing Fe(II) instead of Fe(III), is accomplished here.…”
mentioning
confidence: 99%